2011
DOI: 10.1002/hed.21738
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the peripheral blood levels of interleukin‐12, interleukin‐10, and transforming growth factor‐β in patients with laryngeal squamous cell carcinoma

Abstract: Serum IL-12 or TGF-β levels were not affected with disease activity and classification; however, serum IL-10 levels were correlated with both parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Several groups have reported that IL-10 immunohistochemical staining correlated with clinical outcome in patients with nasopharyngeal carcinoma (102,103), and that IL-10 expression is also associated with FasL (104). In laryngeal SCC, serum IL-10 level was significantly correlated with disease activity and TNM classification (105). These findings suggest that IL-10 production from SCCHN might reflect more aggressive tumor behavior.…”
Section: Tumor Sidementioning
confidence: 85%
“…Several groups have reported that IL-10 immunohistochemical staining correlated with clinical outcome in patients with nasopharyngeal carcinoma (102,103), and that IL-10 expression is also associated with FasL (104). In laryngeal SCC, serum IL-10 level was significantly correlated with disease activity and TNM classification (105). These findings suggest that IL-10 production from SCCHN might reflect more aggressive tumor behavior.…”
Section: Tumor Sidementioning
confidence: 85%
“…However in the current study the serum levels of IL12 in the patients both pre-and posttreatment were not reflective of the survival of patients. The change in serum IL10 without a concurrent change in serum IL12 has however, previously been demonstrated in head and neck cancer patients where it was found that, although levels of the Th2 cytokines IL4, IL6 and IL10 were elevated in cancer patients compared with controls, levels of Th1 cytokines IL2 and GMCSF were also increased and those of IL12 remained the same as controls (19,20). In addition, a trend towards better survival has been found with high expression of IL12 and IL7 within the tumour itself (21) and intratumoural administration of IL12 to HNSCC patients elicits a Th1 profile in the locoregional lymph nodes (22), indicating that the cytokines within the tumour microenvironment may contribute to survival and these need to be determined in addition to those in the circulation.…”
Section: Discussionmentioning
confidence: 95%
“…There was also a significant increase in serum IL-10 levels in patients with T 3–4 stage disease ( p < 0.05). This finding is in accordance with Günaydin et al ., who showed increasing IL-10 detection in laryngeal SCC patients with advanced stage tumours, although the IL-12 level was unaffected by tumour progression 10 . According to Jebreel et al ., serum IL-10 is also more likely to be detected in patients with T 3–4 stage head and neck SCCs 20 …”
Section: Discussionmentioning
confidence: 96%
“…reported significantly higher serum IL-10 levels and Melinceanu et al . reported higher serum IL-6 and IL-10 levels in laryngeal SCC patients than in controls 10 25 According to Eyigor et al ., elevated serum IL-6 and IL-10 concentrations are detectable in both laryngeal SCC and laryngeal dysplasia patients 9 .…”
Section: Discussionmentioning
confidence: 98%